Circulating lipopolysaccharide-binding protein and carotid intima-media thickness in obstructive sleep apnea - Trojová, Ivana; Kozárová, Miriam; Petrášová, Darina; Malachovská, Zuzana; Paraničová, Ivana; Joppa, Pavol; Tkáčová, Ružena (Physiological research, 2018)
Circulating lipopolysaccharide-binding protein (LBP), a metabolic endotoxemia marker, was identified as an independent predictor of atherosclerosis. Although increases in carotid intima-media thickness (CIMT) were repeatedly reported in obstructive sleep apnea (OSA), neither the role of OSA in metabolic endotoxemia nor of LBP in early atherosclerosis were explored in patients with OSA. At a tertiary university hospital we investigated the relationships between OSA, LBP and CIMT in 117 men who underwent full polysomnography and CIMT assessment by B-mode ultrasound. Circulating LBP concentrations and average CIMT increased from patients without OSA to those with mild-moderate and severe OSA (from 32.1+/-10.3 to 32.3+/-10.9 to 38.1+/-10.3 microg.ml(-1), p=0.015; from 0.52+/-0.09 to 0.58+/-0.06 to 0.62+/-0.10 mm, p=0.004, respectively). Oxygen desaturation index (ODI) was a predictor of serum LBP levels independent of age, waist-to-hip ratio (WHR), smoking, hypertension, HDL cholesterol, triglycerides and fasting glucose [p (ANOVA)=0.002, r(2)=0.154], with no independent effect of the ODI*WHR interaction term on LBP. Furthermore, serum LBP predicted CIMT independently of known risk factors of atherosclerosis including obesity (p<0.001, r(2)=0.321). Our results suggest that OSA severity contributes to metabolic endotoxemia in patients with OSA independently of obesity, and that LBP might represent a contributing factor promoting early atherosclerosis in such patients.
Keywords: dospělí; Cross-Sectional Studies; polysomnografie; Humans; lidé středního věku; Cohort Studies; Middle Aged; Carotid Intima-Media Thickness; Acute-Phase Proteins; membránové glykoproteiny; transportní proteiny; Endotoxemia; Risk Factors; mužské pohlaví; endotoxemie; Adult; průřezové studie; Sleep Apnea, Obstructive; rizikové faktory; biologické markery; Membrane Glycoproteins; ženské pohlaví; proteiny akutní fáze; Polysomnography; intimomediální šíře tepenné stěny; lidé; Carrier Proteins; obstrukční spánková apnoe; kohortové studie; Biomarkers; Male; Female